The other side of the Article 21(3) coin: Human rights in the Rome Statute and the limits of Article 21(3). (10th September 2019) - Irving, Emma
Abstract: The drafters of the Rome Statute sought to accord human rights a central place within the legal framework of the International Criminal Court (ICC). This was done not only through numerous provisions on the rights of the accused, victims, and witnesses, but also through the inclusion of the overarching Article 21(3) of the Rome Statute. Article 21(3) Rome Statute requires that the interpretation and application of all ICC law be consistent with internationally recognized human rights. While this provision has been employed on numerous occasions to bolster human rights protection in the ICC legal framework, it is not without its limits. In a series of decisions over the past few years, ICC judges have placed limits on the protections that can be read into the ICC legal framework on the basis of Article 21(3). Beyond stating that the ICC 'is not a human rights court', the decisions in question articulate no clear justification for the limitations imposed on Article 21(3). The present article analyses these decisions and identifies the underlying rationale for the Court's approach: the principle of speciality. However, the picture is further complicated by the judges' willingness to overlook the principle of speciality when particularly serious violations of human rights are involved. This leaves the precise contours of human rights protection in the ICC legal framework undefined.